(3GdEJMGa GdhLjR HCNHGQ GdYOhJjf dehdGfG YHOGdYRjRs - (3eMeO Hf Ydj GdOcGdj GdSdGhj, GdoqOnqcGdj , J (B1364 (3g` s
(3ChdgG (B:s
(3SHMGf ef CHOY GdCchGf hJfRg ef JGQjN GdOghQ hGdCReGf , hHYO aEf GdYde fYeI YXei hGdbOQI Ydi EHdGZg CYXe hCSfi , hef CLd GdYdhe s
(3BNQgG (B:s
(3bGdhG(B: (3hjhLO HNW ehdGfG SdjeGf Ydi gPG GdTQM cKjQ efgG ef eff Gddg Ydi YHOg SdjeGf s
(3jJVef GdNHQ Yf eOjfI SdG HYOhjJgG hhUagG heYGQa gdgG hJQGLe QLGdgGs
(3CgOGg GdeDda Edi ehdGi YHOGdYRjR SfI (B1313(3g`s
(3QGLYI GdTQja GdeDQN Gdehdj ESeGYjd Hf QTjO Hf GdeCehf Hf GdQTjO Hf GdegOj Hf aGQS Hf CejQ GdeDefjf Gdehdj ESeGYjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B11 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs